Analysis of Material Supplier Selection in Laminated Bamboo Shipyards Using the Analytical Hierarchy Process Method - Heri Supomo; Abdul Rachman Safarudin; Wikaranosa Scotiandharu Supomo (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
The material supply chain is an essential part of the shipbuilding industry. For this reason, it is necessary to select suppliers who can support the material needs of ship production. Qualitative and quantitative factors are multi-criteria problems in supplier selection. The Analytical Hierarchy Process (AHP) method effectively determines an integrative approach to supplier selection. This research is applied to a laminated bamboo shipyard to evaluate several companies that can be used as material suppliers. The analysis was carried out using expert choice software by calculating the weight of each criterion and sub-criteria. The analysis results obtained the priority of the primary material supplier with the Kediri area (S1) as the supplier of bamboo material for ship construction with a global weighting value of 0.363. PT. An (S5) located in the Surabaya area is the next top priority as a supplier of adhesive and finishing 1st material components with global weighting values of 0.434 and 0.427, respectively. PT. E (S9) is located in the Semarang area as a priority supplier of finishing 2nd material components with a global weighting value of 0.490. UD. G (S11) is located in the Surabaya area as a priority supplier of ship mold components with a global weighting value of 0.456. In addition, UD. J (S14), located in the Surabaya area, is a priority supplier of material components for clamps, sanding, and cutting blades with a global weighting value of 0.496 and 0.351.